The dosimetric value and safety evaluation of 3D printed bolus in adjuvant intensity-modulated radiotherapy after radical mastectomy for breast cancer: a prospective cohort study - Yaxue Wang; Hanzong Li; Wendie Hu; Bohan Li; Yujie Du; Fengyan Li (Radiation Oncology)
Abstract Purpose Breast cancer patients may use a bolus to increase the dose to skin in radiotherapy after radical mastectomy. The 3D printed bolus (3DPB) specifically customized based on individual conditions offers better conformity. This study aims to provide clinical insights by evaluating the dosimetric benefits and safety of 3DPB in radiotherapy following radical mastectomy for breast cancer. Materials and methods The study included breast cancer patients who received post-mastectomy radiotherapy with 3DPB. Researchers retrospectively collected dose data from patients’ radiotherapy plans, including with and without 3DPB, and prospectively observed the acute and late side effects in the cohort of patients undergoing mixed plan radiotherapy. To compare the dosimetric differences between radiotherapy plans with and without 3DPB, such as the dose distribution data of CTV, PTV, and organs at risk, matched sample T-test was used for data conforming to normal distribution, and non-parametric test was used for data not conforming to normal distribution. P < 0.05 was considered statistically significant. Results A total of 35 patients were included with a median follow-up time of 16 months. In terms of radiotherapy side-effects, no level 4 acute side-effects occurred. A total of 82.2% of the patients had no obvious side-effects. No late radiotherapy side-effects of level 2 or higher occurred. In terms of dosage, radiotherapy plans with 3DPB showed better conformance (P < 0.001) and dose homogeneity (P < 0.001) than plans without 3DPB. The results indicated that the V95% dose of CTV1, CTV2, P-CTV, P-CTV1, and P-CTV2 was higher in the plans with 3DPB than in those without 3DPB (all P < 0.001). Conclusions The use of 3DPB in breast cancer radiotherapy is effective, achieving higher and more uniform dose distribution and better target conformity compared to without 3DPB. Additionally, it is associated with a low incidence of acute and late side effects.